Identifying alternative models of healthcare service delivery to inform health system improvement: scoping review of systematic reviews - Jessup, Rebecca; Putrik, Polina; Buchbinder, Rachelle; Nezon, Janet; Rischin, Kobi; Cyril, Sheila; Shepperd, Sasha; O’Connor, Denise A (BMJ open, 2020)
ObjectiveTo describe available evidence from systematic reviews of alternative healthcare delivery arrangements relevant to high-income countries to inform decisions about healthcare system improvement.DesignScoping review of systematic reviews.Data sourcesSystematic reviews of interventions indexed in Pretty Darn Quick-Evidence.Eligibility criteriaAll English language systematic reviews evaluating the effects of alternative delivery arrangements relevant to high-income countries, published between 1 January 2012 and 20 September 2017. Eligible reviews had to summarise evidence on at least one of the following outcomes: patient outcomes, quality of care, access and/or use of healthcare services, resource use, impacts on equity and/or social outcomes, healthcare provider outcomes or adverse effects.Data extraction and synthesisJournal, publication year, number and design of primary studies, populations/health conditions represented and types of outcomes were extracted.ResultsOf 829 retrieved records, 531 reviews fulfilled our inclusion criteria. Almost all (93%) reviews reported on patient outcomes, while only about one-third included resource use as an outcome of interest. Just over a third (n=189, 36%) of reviews focused on alternative information and communications technology interventions (including 162 reviews on telehealth). About one-quarter (n=122, 23%) of reviews focused on alternative care coordination interventions. 15% (n=80) of reviews examined interventions involving changes to who provides care and how the healthcare workforce is managed. Few reviews investigated the effects of interventions involving changes to how and when care is delivered (n=47, 9%) or interventions addressing a goal-focused question (n=38, 7%).ConclusionA substantial body of evidence about the effects of a wide range of delivery arrangements is available to inform health system improvements. The lack of economic evaluations in the majority of systematic reviews of delivery arrangements means that the value of many of these models is unknown. This scoping review identifies evidence gaps that would be usefully addressed by future research.